Pb2+ Responsive Cu-In-Zn-S Quantum Dots With Low Cytotoxicity - Han, XiaoLe; Yu, Fan; Lei, JiaWen; Zhu, Jiahua; Fu, HaiYan; Hu, JunCheng; Yang, Xiao-Long (Frontiers in Chemistry, 2022)
Water-soluble Cu-In-Zn-S quantum dots (CIZS QDs) with orange fluorescence have been synthesized with a glutathione (GSH) as stabilizer via facile a one-step hydrothermal method. The optimal reaction conditions of CIZS QDs including temperature, time, pH, and the molar ratios of precursors were studied. TEM results indicate that the aqueous-dispersible CIZS QDs are quasi-spherical, and the average diameters are 3.76 nm with excellent fluorescent stability. Furthermore, the cytotoxicity of CIZS QDs was investigated by the microcalorimetry combining with TEM and the IC50 was 10.2 μM. CIZS QDs showed a promising perspective in applications such as a fluorescent probe for bioimaging and biolabeling due to the low cytotoxicity and good biocompatibility. Moreover, the CIZS QDs can distinguish Pb2+ ion from other ions, offering great potentials in lead ion determination in drinking water. According to the results of UV, XRD, FL, PL, and ITC methods, the mechanism of CIZS QDs-Pb2+ assay is due to hydrogen bonding or van der Waals forces in the formation of Pb2+ and CIZS QDs.